Prevention Policy in Controlling Narcotics Circulation in Cirebon Detention Center - Suwirno Suwirno (Jurnal Media Hukum, 2019)
The lack of control from the authority has opened the opportunity for the prisoners to do transaction of narcotis in the prison. Circulation of narcotics in the prisons involves complex networks. This paper aims to explore the policies made to prevent narcotics circulation in Cirebon Detention Center. The research was carried out through both library-based study and field work.  It is found that the legal system needs to be improved in order to address the problems of narcotics circulation in detention center. The improvement is necessary to all aspect of legal system that is legal substance, legal structure, and legal culture.